Accumulation of activated lymphocytes in liver of Listeria factor Ei treated rabbits - Janoutovă, J; Măra, M; Likovsky, Z (Folia microbiologica, 1995)
Factor Ei isolated from Listeria monocytogenes caused in rabbits 1 d after intravenous administration activation of peripheral blood lymphocytes in terms of rRNA biosynthesis. Increase of the number of these active lymphocytes was observed not only in peripheral blood, but also in spleen, lung, kidney, and liver. when the number of lymphocytes was related to the amount of the organ tissue cells, the increment appeared significant only in the liver where the number of active lymphocytes exceeded the control value by one order of magnitude. Based upon this observation we concluded that the accumulation of Listeria factor Ei activated lymphocytes occurred in liver. This characteristic is considered an additional immunomodulative property of Listeria factor Ei similar to the Escherichia coli lipopolysaccharide.
Keywords: počet lymfocytů; Rabbits; králíci; aktivace lymfocytů; Lymphocyte Activation; Listeria monocytogenes; Lymphocyte Count; ledviny; játra; Spleen; Animals; Liver; biologické faktory; podskupiny lymfocytů; zvířata; Biological Factors; slezina; Kidney; Lymphocyte Subsets